The Legal and Regulatory Review on the Implementation of Green Construction in Indonesia - Imanto, Yuwono; Sami'an, Sami'an; Hardjomuljadi, Sarwono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The implementation of green construction concept in Indonesia's construction industry is increasing as a response to the need for sustainable development. However, the application of this concept is not without challenges, which can heighten the potential for legal and regulatory issues. This study aims to explore the implications of green construction implementation from technical, legal, environment and regulatory perspectives.This research approach was conducted using qualitative methods, with data collected from literature and interviews with experts who involved in green construction. Data is gathered through literature studies and confirmation results using the Delphi method. The findings reveal that a lack of comprehensive understanding of green construction principles often leads to potential disputes among stakeholders, particularly in risk management, responsibility allocation, and different interpretations of technical and legal aspects.The study identifies key challenges such as additional cost for eco-friendly technologies and non-compliance with green building standards and government regulations as major contributors to legal issues likewise. To mitigate these risks, harmonization of regulations, strengthening of contract documents, and dissemination of green construction knowledge among stakeholders are essential.This study provides recommendation for construction industry player to manage potential legal issues in construction contract while supporting the more effective implementation of green construction in Indonesia. Keywords: Green Construction, Legal issues, Green Building